Distal Radius Fractures: Evaluation of Closed Reduction and Percutaneous Kirschner Wire Pinning - Özkan, Sezai; Westenberg, Ritsaart F.; Helliwell, Lydia A.; Mudgal, Chaitanya S. (Journal of Hand and Microsurgery, 2018)
Objective Closed reduction and percutaneous pinning (CRPP) is losing popularity as a treatment modality for distal radius fractures. However, in select cases, CRPP may have advantages relative to open reduction and internal reduction. We aimed to retrospectively assess the outcomes after CRPP for the treatment of distal radius fractures.Study Design This is a retrospective cohort study.Methods We used billing records to identify all skeletally mature patients with a distal radius fracture who were treated with CRPP by a single surgeon at a level I trauma center in an urban city in the United States. We assessed the medical charts and recorded demographics, trauma and treatment characteristics, radiographic characteristics, and outcomes.Results All patients had a good or excellent range of motion regarding forearm rotation, and almost 80% had good or excellent range of motion regarding flexion or extension of their wrist. One patient had a concern for pin tract infection, and one had subcutaneous migration of a pin, which were both treated by pin removal.Conclusion CRPP is a good option in patients with few and sizeable fracture fragments in patients with a distal radius fracture, and it should be considered as an effective tool to restore radiographic parameters and functional outcomes.
Keywords: closed reduction and percutaneous pinning; Kirschner wire; open reduction and internal fixation; distal radius fracture